Problem-based learning in the life science classroom, K-12 - McConnell, Tom J., 1962-; Parker, Joyce, 1955-; Eberhardt, Janet, 1952- (National Science Teachers Association, 2016)
This book explores problem-based learning (PBL) in the life sciences curriculum. It shows how to engage students with scenarios that represent real-world science in the areas of life cycles, ecology, genetics, and cellular metabolism, and will prompt K-12 learners to work collaboratively on analyzing problems, asking questions, posing hypotheses, finding needed information, and then constructing a proposed solution.